Nuclear speckles are regulatory hubs for viral and host mRNA expression during HSV-1 infection - Shani Nadav-Eliyahu; Chaya Bohrer; Alon Boocholez; Noa Kinor; Vesa Aho; Jennifer I. C. Benichou; Salla Mattola; Sami Salminen; Henri Niskanen; Minna U. Kaikkonen; Maija Vihinen-Ranta; Yaron Shav-Tal (Proceedings of the National Academy of Sciences, 2026)
Herpes simplex virus type 1 (HSV-1) infection remodels the host nucleus, marginalizing chromatin and forming viral replication compartments (VRCs). Nuclear speckles, nuclear bodies enriched in RNA-processing factors, reposition around VRCs and undergo structural changes. While viral mRNAs are transcribed in VRCs and host transcription is largely suppressed, the nuclear routes used by viral and upregulated host transcripts and their relationship with nuclear bodies remain unclear. We show that immediate-early (IE) viral transcripts uniquely accumulate in nuclear speckles prior to export, unlike early or late transcripts, revealing a selective nuclear speckle-dependent pathway. Similarly, host mRNAs upregulated during infection traffic into nuclear speckles after transcription. Moreover, nuclear speckles are structurally remodeled, marked by the long non-coding RNA (lncRNA) MALAT1 removal and increased dynamics of the nuclear speckle core protein SRRM2. Finally, we found that blocking mRNA export causes IE transcripts to accumulate in nuclear speckles and that nuclear speckle disassembly severely impairs IE mRNA export, preventing downstream viral gene expression. These findings establish nuclear speckles as dynamic regulatory hubs that selectively facilitate the processing and export of IE viral mRNAs during HSV-1 infection.